Suicide risk transition and cumulative incidence post-cancer diagnosis: retrospective cohort study utilizing population-based cancer registry in Japan - Kaname Watanabe; Sho Nakamura; Choy-Lye Chei; Hiroto Narimatsu (BMC Cancer)
Abstract Background Suicide risk in cancer patients peaks early post-diagnosis; however, detailed studies on its changes are scarce. We analyzed population-based cancer registry data to identify trends in suicide risk and incidence following diagnosis among cancer patients. Methods Data of cancer patients who died between 2016 and 2018 were used for descriptive analysis, while data of patients who were newly diagnosed during the same period were used to calculate standardized mortality ratios (SMRs) and conduct survival and multivariable analyses. The diagnostic data included follow-up information through the end of 2019. All data were obtained from the Kanagawa Cancer Registry. The SMRs for suicide were calculated every 3 months up to 48 months post-diagnosis. Cumulative incidences of suicide were calculated using survival analysis. Risk factors associated with suicide were identified with multivariable analysis using the Fine and Gray method. Results Among the 105 598 cancer patients who died during the study period, 282 patients (0.27%) died by suicide. The SMRs of suicides were 2.71 (95% confidence interval [CI]: 1.99–3.60) and 2.10 (95% CI: 1.64–2.66) up to 6 months and 1 year post-diagnosis, respectively. The maximum change in the 3-month interval SMR was 3.45 (95% CI: 2.34–4.89) within the first 3 months, subsequently decreasing to the same level as that of the general population and temporarily increasing again in 13–15 months. In the survival analysis, the cumulative suicide rates at 6 and 12 months were 0.23% and 0.33%, respectively. In the multivariate analysis, suicide risk was significantly higher in patients with intermediate or poor prognosis cancer sites and lower in females. Conclusions Suicide among cancer patients is a rare event in the aggregate, but it still occurs in small numbers and should be addressed. The bimodal increase in SMR suggests the influence of adverse outcomes, such as cancer diagnosis, recurrence, and metastasis.